Hukum Multi Akad Dalam Fikih Muamalah - Hasanudin Hasanudin (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Modern financial transactions are increasingly complex and some of them are new things that did not exist in the past. The existing contracts in fiqh are not able to accommodate these transactions so that scholars try to combine several contracts for one transaction. The combination of these contracts gave birth to multiple contracts. By analyzing the opinions of scholars, it is found that the multi-contract law is debated among scholars. The majority of scholars view it as a justified innovation but some other scholars forbid it based on the hadith of the Prophet. This difference in scholars has an impact on the permissibility of using these multi-contracts in modern transaction activities.Keywords: Multi Contract; Law; Usury; Muamalah Fiqh Abstrak: Transaksi keuangan modern semakin kompleks dan sebagiannya merupakan hal baru yang tidak ada di zaman dulu. Akad-akad yang ada dalam fikih tidak mampu mewadahi transaksi tersebut sehingga ulama berupaya melakukan kombinasi beberapa akad untuk satu transaksi. Kombinasi akad tersebut melahirkan multi akad. Dengan menganalisis pendapat ulama ditemukan bahwa hukum multi akad diperdebatkan di kalangan ulama. Mayoritas ulama memandangnya sebagai inovasi yang dibenarkan namun sebagian ulama lainnya mengharamkan berdasarkan hadis Nabi. Perbedaan ulama ini berdampak pada kebolehan penggunaan multi akad tersebut dalam kegiatan transaksi modern.Kata Kunci: multi akad, hukum, riba, fikih muamalah